Cyprus and the EU: Dispute Resolution as an International Public Good? - Ugur, Mehmet (Études helléniques / Hellenic Studies, 2003)
This article applies the concept of international public goods ro conflict resolution, with a view to assess the causes and likely consequences of the European Union's increased involvement in the Cyprus problem. lt identifies the conditions under which the EU could facilitate the production of regional public goods in general, the resolution of the Cyprus problem in particular. The existing evidence suggests that the EU has gradually assurned the role of a rule setter that would induce the parries to contribute to the resolution of the Cyprus problem as: (i) EU member states' Cyprus policies have become convergent; (ii) the establishment of a Cypriot state has become incentive-compatible for both Greek and Turkish-Cypriots; and (iii) the Greek, Turkish, and Cypriot governments' willingness to comply with EU rules has increased as a result of either EU membership or prospect thereof.